Patulin production by Byssochlamys spp. in fruit juices. - Rice, S L (1977)
Ten strains of Byssochlamys fulva and three strains of B. nivea were cultured in a laboratory medium and tested for their ability to produce patulin. Two strains of B. fulva and all three strains of B. nivea produced the mycotoxin. One strain of B. fulva produced patulin in 11 of 13 processed fruit juices, with greatest amounts being produced in blueberry, red raspberry, and boysenberry juices, whereas no patulin was detected in prune or tomato juices. Grown in Concord grape juice at 18, 25, 30, and 38 degrees C, this strain produced the highest patulin concentration at 18 degrees C after 25 days, whereas biomass production was greatest at 25 and 30 degrees C after 20 and 25 days.